2021
DOI: 10.3390/plants10112380
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Molecular Regulation Mechanisms of Slow Ripening Trait in Prunus persica

Abstract: Fruit development is a complex process that involves the interplay of cell division, expansion, and differentiation. As a model to study fruit development, nectarines incapable of ripening were described as slow ripening. Slow ripening fruits remained firm and exhibited no rise in CO2 or ethylene production rates for one month or more at 20 °C. Different studies suggest that this trait is controlled by a single gene (NAC072). Transcriptome analysis between normal and slow ripening fruits showed a total of 157,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…This last homozygous deletion presents a phenotype that stops fruit development in the S2 stage (slow ripening) [12]. Transcriptomic analysis has revealed that the absence of this transcription factor generates differences in the expression of key genes involved in the abscisic acid (ABA) and gibberellic acid (GA) biosynthesis pathways in the early stages of fruit development [13].…”
Section: Introductionmentioning
confidence: 99%
“…This last homozygous deletion presents a phenotype that stops fruit development in the S2 stage (slow ripening) [12]. Transcriptomic analysis has revealed that the absence of this transcription factor generates differences in the expression of key genes involved in the abscisic acid (ABA) and gibberellic acid (GA) biosynthesis pathways in the early stages of fruit development [13].…”
Section: Introductionmentioning
confidence: 99%